(untitled) (Al-Academy, 2021)
We live in a world where cultures and visions overlap .. Therefore, every society seeks to create a harmonization that is in line with the data of those special cultures and reproduces those cultures and defines their paths. There are cultures based on historical action and experience and others that work on historical displacement, and art is one of the most important means of transmitting cultures and establishing their aesthetic harmony. This research is concerned with studying (cultural patterns and their representations in contemporary Mexican painting) and it falls into four chapters. The first chapter is devoted to explaining the research problem, its importance, the need for it, the goal of the research, and identifying the most important terms contained in it. The research problem crystallized around the monitoring of cultural patterns and their representations carried on Mexican painting, and what it bears. These patterns are of the explicit and implicit meanings and connotations of Mexican history and culture, within the space of contemporary art. Hence, the current research problem arose through the following question: - How are the cultural systems represented in contemporary Mexican art? The research has one goal: to know the representations of cultural patterns in Mexican art.The second chapter included two papers on me, the first with a study of (the concept of pattern and its cultural connotations), while the second research concerned the study of (contemporary trends in Mexican art), while the third chapter concerned the research procedures (the research community, the research sample, its methodology, and the analysis of the research sample samples). The research ended with the fourth chapter, which included the results of the research, its conclusions, the research sources, appendices and the research summary in English.